Hubungan stres terhadap kelelahan pada mahasiswa Fakultas Kedokteran Universitas Udayana - Adela Nathania; I Made Krisna Dinata; I Putu Adiartha Griadhi (Intisari Sains Medis, 2019)
Background: Stress can cause mental and physiological changes in a person's body, by activating the HPA axis and the autonomic nervous system. As a result, catecholamines and cortisol will be secreted and cause changes to the additional energy reserves by the body to deal with stressors and the emergence of introseptive stimuli. This energy can be depleted, causing a person to no longer have the energy to continue their activities, while introseptive stimuli cause fatigue and decreased motivation.Methods: This analytic observational study was designed in the form of a cross sectional study of questionnaire data to measure stress and fatigue, that is distributed to 300 students of education programs for doctors in 2nd, 4th, and 6th semester of Faculty of Medicine Udayana University in 2018. General Health Questionnaire - 12 (GHQ-12) and the 30 item Fatigue Questionnaire was used to measure stress and fatigue.Result: 262 samples met the inclusion and exclusion criteria, 23.7% of students experiencing stress, 1.1% experienced very high fatigue, 12.2% experienced high fatigue, 56.9% experienced moderate fatigue, and 29.8 % experience low level fatigue. Stress has a significant effect with a significance value is 0.000.Conclusion: Stress has a relationship with fatigue in students of the Faculty of Medicine Universitar Udayana, in Bachelor of Medicine and Professionals Doctor Study Program.